Animal farm: a fairy story (Signet Classic, Recorded Books, Blackstone Audiobooks, 1987)
"When the animals at Manor Farm revolt against their master, Mr. Jones, their goal is to take over the farm and establish an ideal community based on hard work, honesty, and the equality of all animals. Guided by the memory of Old Major's utopian vision and the seven commandments, Animal Farm, as the animals have renamed it, briefly fulfills the ideal."--Container.

Fahrenheit 451 (Brilliance Audio on compact disc, ,, 2018)
In a future totalitarian state where books are banned and destroyed by the government, Guy Montag, a fireman in charge of burning books, meets a revolutionary schoolteacher who dares to read and a woman who tells him of a past when people did not live in fear.

Brave new world (Harper Perennial modern classics, ,, 2008)
First published 70 years ago, the classic, prophetic novel capturing the socialized horrors of a futuristic utopia remarkably explores the now-timely themes of cloning, individual creativity and freedom, and the role of science, technology, and drugs in humankind's future.

Un mundo feliz (Contemporánea), ,, 2022)
"Touching on themes of control, humanity, technology, and influence, Aldous Huxley's enduring classic is a reflection and a warning of the age in which it was written, yet remains frighteningly relevant today."--

1984 (Contemporánea), ,, 2013)
"En el año 1984 Londres es una ciudad lúgubre en la que la Policía del Pensamiento controla de forma asfixiante la vida de los ciudadanos. Winston Smith es un peón de este engranaje perverso, su cometido es reescribir la historia para adaptarla a lo que el Partido considera la versión oficial de los hechos... hasta que decide replantearse la verdad del sistema que los gobierna y somete."--Amazon.

Brave new world: and, Brave new world revisited (HarperCollins, 2004)
The astonishing novel Brave New World, originally published in 1932, presents Aldous Huxley's vision of the future-of a world utterly transformed. Through the most efficient scientific and psychological engineering, people are genetically designed to be passive and therefore consistently useful to the ruling class. This powerful work of speculative fiction sheds a blazing critical light on the present and is considered to be Huxley's most enduring masterpiece. Following Brave New World is the nonfiction work Brave New World Revisited, first published in 1958. It is a fascinating work in which Huxley uses his tremendous knowledge of human relations to compare the modern-day world with the prophetic fantasy envisioned in Brave New World, including threats to humanity, such as overpopulation, propaganda, and chemical persuasion.

The Lost (Witch & wizard, 5, 1, 2014)
Detective Tom Moon and his multi-talented team face off against an international crime ring looking to seize control of America's most vibrant city, Miami. The city of Miami is Detective Tom Moon's back yard. He's always kept it local, attending University of Miami on a football scholarship, and, as a Miami PD officer, protecting the city's most vulnerable. Now, as the new leader of an FBI task force called "Operation Guardian," it's his mission to combat international crime. Moon's investigative team discovers that the opportunistic "Blood Brothers" -- Russian nationals Roman and Emile Rostoff -- have evaded authorities while building a vast, powerful, and deadly crime syndicate throughout Europe and metropolitan Miami. Moon played offense for U of M, but he's on the other side of the field this time. And as the Rostoffs zero in on a target dear to Tom, they're not playing by anyone's rules.